Synthesis of 2-[(5-Amino-1H-pyrrol-2-yl)sulfanyl]acetic Acid Esters: One-Pot Assembly from Propargyl Amines, Isothiocyanates, and Alkyl 2-Bromoacetates - Tarasova, Olga A.; Nedolya, Nina A.; Albanov, Alexander I.; Trofimov, Boris A. (Synthesis, 2019)
2-[(5-Amino-1H-pyrrol-2-yl)sulfanyl]acetic acid esters have been synthesized in up to 77% yield by the one-pot reaction of lithiated propargylamines with isothiocyanates followed by sequential treatment with t-BuOK–DMSO and alkyl 2-bromoacetates. The process occurs through the initial formation of the thiophene core, followed by its recyclization into the pyrrole nucleus at a higher temperature (ca. 45–60 °C).
Keywords: 2-[(5-amino-1H-pyrrol-2-yl)sulfanyl]acetic acid derivatives; lithiated propargylamines; isothiocyanates; alkyl 2-bromoacetates